How the Al-Quds Bard MAT Program Changed Mathematics’ Teachers in Their Classrooms - Jaber, Nadia; Jeanne Albert (European Journal of Multidisciplinary Studies, 2017)
In this paper, we are going to analyse the situation in math classes in Nablus Directorate depending on reports written by their supervisor. Also we are looking at AQB courses in MAT (Master of Arts in Teaching) program for math teachers and supervisors, discussing the syllabus of these courses, in particular relating to a math supervisor. We will show how the courses met the needs of this supervisor in her work with teachers. We will concentrate on the effectiveness of using Action Research as an important strategy for MAT program in developing this supervisor’s educational skills. In the third part we are going show how the assignments and the emphasis in the use of qualitative research, greatly affected the supervisor. We will also compare between teachers’ work in their math classrooms before and after being in workshops organized by this supervisor who is now a graduate of the MAT program. Finally, the data was collected and analysed to describe how participation in the Al-Quds Bard MAT program changed this mathematics supervisor’s workshops and how it greatly affected teachers’ work in their classrooms.